THE REQUEST FOR PRELIMINARY RULING AND PRACTICE IN THE REPUBLIC OF CROATIA (EU and comparative law issues and challenges series (ECLIC), 2019)
The Republic of Croatia joined the European Union on 1 July 2013 marking the end of a process which started in 2001 with the signing of the Stabilisation and Association Agreement. Membership in the Union brought significant changes in Croatian legal practice, particularly in its case law. Reference-based relationship between national courts and the Court of Justice of the European Union (CJEU) calls for changes in existing perspective. National courts are under an obligation to give full effect to applicable provisions of EU law and, if necessary, to refuse of their own motion application of any conflicting provision of national legislation. Furthermore, the existence of a rule of national law whereby courts against whose decisions there is a judicial remedy are bound on points of law by the rulings of a court superior to them cannot deprive the lower courts of the right provided for in Article 267 of the Treaty on the Functioning of the European Union (TFEU) to refer questions on the interpretation of EU law to the CJEU. From the outset, the author will lay down general remarks on the preliminary ruling procedure, on the scope and relevance of Article 267 TFEU and on the national court’s perspective. While discussing the application of EU law in Croatia, the focus will be on the “shift” of powers between legislative and judicial authority arising from direct effects and supremacy of EU law. Namely, the duty of national courts to set aside incompatible national legislation on their own motion amounts to a derogation of existing national legislation. Deciding cases by applying directly applicable EU legislation calls for no prior legislative activity on the side of national legislator. The application of EU law in Croatia also calls for modification of existing judicial hierarchy. Rules of binding decisions of superior courts do not apply as they did since the lower courts still have the right to refer questions of interpretation of EU law to the CJEU whenever in doubt about the correct interpretation of EU law. There is also a matter of possible „bypassing“ of the Constitutional Court (in case of provision of national law that is not only contrary to EU law, but also unconstitutional) that will be addressed. Statistics and summarised analysis of CJEU case law on request for preliminary rulings from Croatia will be given as well as references to subsequent case law of domestic courts. The emphasis will be put on the issues raised so far, namely Article 18 of the Criminal Procedure Act and the case law of Supreme Court of the Republic of Croatia on staying criminal procedure when the request for the preliminary ruling has been made. Also, reference will be made to the existing case law on staying civil procedures when the request for the preliminary ruling has been made.